PROFIL KEDISIPLINAN PESERTA DIDIKKELAS VIII SMP NEGERI 1 CILAWU GARUT - Suharso Suharso; Ika Mustika; Ecep Supriatna (IKIP Siliwangi, 2019)
The purpose of this study is to know the picture of student learning discipline grade VIII of SMP Negeri 1 Cilawu Garut The method used is descriptive quantitative research with a learning discipline scale data collection tool and learner observation sheets in class. The results showed that student learning discipline was in the medium category. Discipline of learning by sex shows that the discipline of learning of female students (87,02) is better than the discipline of learning of male students (74,15). The results of the study of disciplinary learning in terms of aspects of learning discipline were found that students' sense of responsibility was in the low category, while the obedience and timeliness aspects were in the medium category.Keywords: : Discipline learning., Students